Digital Stories as a Creative Assignment for Studying World Religions - Chesnavage, Charles S. (Religions, 2021)
The incorporation of creative assignments in the form of digital stories and artistic assignments in undergraduate and graduate World Religions courses has resulted in positive feedback from the students, and these courses were considered the favorite of the semester. They have given students, many of which identify as “spiritual but not religious”, or “non-practicing”, an opportunity to connect themes from various world religions to their own life stories, implicitly or explicitly. The purpose of this article is to encourage educators in both a secondary and a college/university/seminary setting to consider digital stories as a creative assignment that deepens their understanding of world religions within the context of a World Religions course, or other religion and religious education courses. This article will present the institutional support provided by Mercy College (Dobbs Ferry, New York) and the context for the World Religions class in which the digital stories are assigned. It will be followed by the process of making a digital story, the directions given to the students, the different platforms that students can choose to make the digital stories, and examples of digital stories created by the students. The paper will conclude with a summary of comments made by the students about the assignment and connections with additional articles on the benefits of digital stories to increase empathy and replace the dominant stories that cause oppression and injustice, like racism and white supremacy, with stories that offer resistance and counter the status quo of oppression and injustice.